QUANTIFICATION OF GLYCYRRHIZIN BIOMARKER IN GLYCYRRHIZA GLABRA RHIZOME AND BABY HERBAL FORMULATIONS BY VALIDATED RP-HPTLC METHODS - Alam, Prawez; Foudah, Ahmed I.; Zaatout, Hala H.; Kamal, Y T; Abdel-Kader, Maged S. (African Journal of Traditional, Complementary and Alternative Medicines, 2017)
Background: A simple and sensitive thin-layer chromatographic method has been established for quantification ofglycyrrhizin in Glycyrrhiza glabra rhizome and baby herbal formulations by validated Reverse Phase HPTLC method.Materials and Methods: RP-HPTLC Method was carried out using glass coated with RP-18 silica gel 60 F254S HPTLCplates using methanol-water (7: 3 v/v) as mobile phase.Results: The developed plate was scanned and quantified densitometrically at 256 nm. Glycyrrhizin peaks fromGlycyrrhiza glabra rhizome and baby herbal formulations were identified by comparing their single spot at Rf = 0.63 ±0.01. Linear regression analysis revealed a good linear relationship between peak area and amount of glycyrrhizin in therange of 2000-7000 ng/band.Conclusion: The method was validated, in accordance with ICH guidelines for precision, accuracy, and robustness. Theproposed method will be useful to enumerate the therapeutic dose of glycyrrhizin in herbal formulations as well as in bulkdrug.